FENOMENA DINAMIKA KEPUBLIKAN DALAM HIRARKI RUANG KAWASAN PUBLIK KOTA - Ully Irma Maulina Hanafiah; Doddy Friestya Asharsinyo (Universitas Batam, 2021)
The public area of the city in general is currently experiencing rapid development due to economic growth and the influence of globalization. The public space is formed based on economic, social, political cultural interests, as well as developments and changes that occur in the current public space, making it limited and cannot be accessed optimally by the wider community. This is caused by the hierarchy of public spaces that are formed based on the functions that surround them. The purpose of this study is to reveal the phenomenon of public hierarchy in urban space in the context of its changes. This research is descriptive-analytical and based on theoretical and empirical elaboration. This approach is used to read public spaces in urban areas to get a reference for the interpretation of theoretical relationships from an empirical condition.